2011
DOI: 10.7224/1537-2073-13.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Nintendo Wii Fit Among People with Multiple Sclerosis

Abstract: We examined the potential of Nintendo Wii Fit (Nintendo Co, Ltd, Kyoto, Japan) to increase physical activity (PA) behavior and health among people with multiple sclerosis (MS). The study consisted of a repeated-measures design with a baseline control period and involved 30 people with MS who had the ability to walk 25 feet with or without a cane (26 individuals were included in the analyses). Nintendo Wii was set up in the homes of participants, who were prescribed a Wii Fit exercise program lasting 14 weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 47 publications
1
57
0
4
Order By: Relevance
“…Using the Wii in home-based training can prevent falls in PwMS (Table 1), 28,31 but only Prosperini et al reported that after training had ceased were the improvements in standing balance maintained. 28 Even though these improvements are encouraging, Wii training at home appears to have a smaller effect than other balance rehabilitation approaches.…”
Section: The Current State Of Exergaming Research In Pwmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the Wii in home-based training can prevent falls in PwMS (Table 1), 28,31 but only Prosperini et al reported that after training had ceased were the improvements in standing balance maintained. 28 Even though these improvements are encouraging, Wii training at home appears to have a smaller effect than other balance rehabilitation approaches.…”
Section: The Current State Of Exergaming Research In Pwmsmentioning
confidence: 99%
“…Exergaming may be more enjoyable than other forms of activity, 45 but in order to maximize the benefits of PA, exergaming would need to be used over longer periods than currently reported in the literature, and because of this it is very likely that the novelty would wear-off. 31 Exergames are not a "magic pill" or panacea for all rehabilitative needs, 3,31 but they do have their place as an adjunct to traditional therapy/exercise and in order to exploit this potential bespoke exergames need to be developed using a multi-disciplinary approach. Bespoke exergames offer the ability to alter the game and to meet the needs of the individual.…”
Section: Future Directions For Exergaming Research In Pwmsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found in our study involving the evaluation of Nintendo Wii Fit in the home over a 14-week period that individuals with MS stopped playing once the novelty wore off and contacts had ceased with the patient. We concluded that the Nintendo Wii Fit does not appear to be the "magic pill" to promote long-term participation in physical activity, and that user characteristics (e.g., gender, race, disability level, past experiences and attitudes towards video games) might influence the types of exergames that patients like to play and the type of strategies that should be implemented to promote adherence [66]. A "one-sizefits-all" approach to delivering exergaming interventions may result in non-adherence.…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 94%
“…Overall, 4 studies, [34,36,39,40], exhibited at least 4 types of bias out of a potential 7. One study [35] scored highly in the risk of bias for both performance and detection bias.…”
Section: Critical Appraisal Of Included Studiesmentioning
confidence: 99%